2013
DOI: 10.1371/journal.pone.0059605
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Protective Immune Responses Induced by Pneumococcal Surface Protein A in Fusion with Pneumolysin Derivatives

Abstract: Pneumococcal surface protein A (PspA) and Pneumolysin derivatives (Pds) are important vaccine candidates, which can confer protection in different models of pneumococcal infection. Furthermore, the combination of these two proteins was able to increase protection against pneumococcal sepsis in mice. The present study investigated the potential of hybrid proteins generated by genetic fusion of PspA fragments to Pds to increase cross-protection against fatal pneumococcal infection. Pneumolisoids were fused to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 47 publications
6
48
0
2
Order By: Relevance
“…Another approach is to create fusion proteins, including a lipid motif, as shown here with the fusion of SP_2108 and SP_1912. Such enhancement of immunogenicity and protection against pneumococcal colonization by fusion of proteins had been previously demonstrated with pneumolysin, a TLR4 agonist (39)(40)(41). Here we show this with a TLR2 agonist fused to the antigenic cargo, which likely enhances MHC class II (MHC-II) presentation (42).…”
Section: Discussionsupporting
confidence: 74%
“…Another approach is to create fusion proteins, including a lipid motif, as shown here with the fusion of SP_2108 and SP_1912. Such enhancement of immunogenicity and protection against pneumococcal colonization by fusion of proteins had been previously demonstrated with pneumolysin, a TLR4 agonist (39)(40)(41). Here we show this with a TLR2 agonist fused to the antigenic cargo, which likely enhances MHC class II (MHC-II) presentation (42).…”
Section: Discussionsupporting
confidence: 74%
“…More than one pneumococcal protein can be prepared as a mixture or as fusion proteins. Some studies have demonstrated that fused antigens may be more effective than mixed formulations (Goulart et al, 2013;Lu et al, 2009;Nguyen et al, 2011). In our study, we found that sometimes mixing two or more antigens as the vaccine did not yield the predicted enhanced effect and may even result in a worse outcome than that obtained with just each of the proteins alone (data not shown).…”
Section: Discussionmentioning
confidence: 44%
“…To evaluate the neutralizing capacity of antisera containing anti-Ply antibodies, a hemolysis inhibition assay was performed as described previously (30). Briefly, pooled antisera (1:80) were incubated with Ply, and 2% sheep red blood cells were added.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we selected a PspA molecule able to induce antibodies with broad cross-reactivity (29) and demonstrated the potential use of this PspA molecule in fusion with PdT (30). Recently, in order to improve the immunogenicity of this fusion protein, we constructed a recombinant BCG (rBCG) strain expressing the PspA-PdT fusion protein (rBCG PspA-PdT) (31).…”
mentioning
confidence: 99%